Pengaruh PENGARUH DIVERSIFIKASI PENDAPATAN, UKURAN BANK DAN KOMPETISI BANK TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Paramitha, Devi; Prasetya, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The bank carries out diversification activities to increase income and reduce risks arising from the main activities of the bank as well as being one of the bank's strategies to strengthen banking competitiveness supported by bank size. The market share of Islamic banks which has been low for the last 31 years is still low at around 7%, besides that the growth of fintech which continues to increase makes Islamic banks a good strategy to maintain their performance. This study uses the technique of multiple linear regression analysis of panel data, on 10 Indonesian BUS for the 2015-2021 quarter period. We found that income diversification had an effect on the profitability of Islamic commercial banks for the 2015-2021 period as measured by ROA and ROE, while bank size had an effect on ROA and had no effect on ROE while banking competition had no effect on profitability of Islamic bank and the structure of Islamic bank is in monopolistic market structure.